1995
DOI: 10.1128/mcb.15.12.7050
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of the Alpha/Beta Interferon-Stimulated Jak/Stat Pathway by the SH2 Domain-Containing Tyrosine Phosphatase SHPTP1

Abstract: Interferons (IFNs) induce early-response genes by stimulating Janus family (Jak) tyrosine kinases, leading to tyrosine phosphorylation of Stat transcription factors. Previous studies implicated protein-tyrosine phosphatase (PTP) activity in the control of IFN-regulated Jak/Stat signaling, but the specific PTPs responsible remained unidentified. We have found that SH2 domain-containing PTP1 (SHPTP1; also called PTP1C, HCP, or SHP) reversibly associates with the IFN-␣ receptor complex upon IFN addition. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
261
0
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(274 citation statements)
references
References 54 publications
11
261
0
2
Order By: Relevance
“…Evidence from both in vitro and in vivo studies indicated that tyrosine phosphatases can act as positive as well as negative regulators of the IFN␣/␤-induced Jak/Stat pathway (17,21,22). Recently, we were able to demonstrate that the SH2 domain containing tyrosine phosphatase PTP1C (SHPTP1, HCP, or SHP) functions as a suppressor of IFN␣/␤ signal transduction in hematopoietic cells by specific down-modulation of Jak1 tyrosine phosphorylation (23). Studies of Stat activation by IFN␣/␤ in cell homogenates provided evidence that a tyrosine phosphatase is also required to initiate signal transduction (17).…”
mentioning
confidence: 99%
“…Evidence from both in vitro and in vivo studies indicated that tyrosine phosphatases can act as positive as well as negative regulators of the IFN␣/␤-induced Jak/Stat pathway (17,21,22). Recently, we were able to demonstrate that the SH2 domain containing tyrosine phosphatase PTP1C (SHPTP1, HCP, or SHP) functions as a suppressor of IFN␣/␤ signal transduction in hematopoietic cells by specific down-modulation of Jak1 tyrosine phosphorylation (23). Studies of Stat activation by IFN␣/␤ in cell homogenates provided evidence that a tyrosine phosphatase is also required to initiate signal transduction (17).…”
mentioning
confidence: 99%
“…Based on the observation that there is a good correlation between tyrosine dephosphorylation and inactivation of both Jak and STAT proteins, the roles of protein-tyrosine phosphatases in down-regulating the Jak-STAT pathways have been suggested. Indeed, there is genetic and biochemical evidence indicating that protein-tyrosine phosphatases are critical in regulating distinct Jak kinases within specific cytokine receptor complexes (13)(14)(15). The evidence for the involvement of specific protein-tyrosine phosphatases in dephosphorylating STAT proteins, however, is more indirect (16 -18).…”
mentioning
confidence: 99%
“…Moreover, Jak kinases in macrophages from motheaten mice were found to be hyperphosphorylated following IFN␣/␤ treatment. 24 Our recent study demonstrates that SHP-1 directly binds to the Jak family kinases via a region in its N-terminus independently of SH2/phosphotyrosine interactions. 36 As this interaction leads to SHP-1 activation and the dephosphorylation of Jak kinases, it may be a critical factor required for specific and efficient dephosphorylation of SHP-1 substrates.…”
Section: Introductionmentioning
confidence: 91%
“…This association leads to the activation of SHP-1 PTPase 19,20 and the down-regulation of signaling by the dephosphorylation of substrates. A number of membrane molecules have been found to associate with SHP-1 via its SH2 domains, including receptors of hematopoietic growth factors and cytokines, [21][22][23][24][25] subunits of the B cell antigen receptors [26][27][28][29] and the inhibitory receptor of natural killer cells. 30 The functional significance of these associations is underscored by the increased signaling from these membrane molecules in motheaten hematopoietic cells which lack functional SHP-1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation